Designing a multifunctional nanoplatform based on PEGylated cobalt ferrite magnetic nanoparticles containing capecitabine for cancer theranostics - Poorhossein, Mohammad; Pishbin, Fatemehsadat; Ataie, Abolghasem; Akrami, Mohammad (Ceramics International, 2023)
Anticancer drugs can be delivered more efficiently to tumor sites with fewer side effects by utilizing magnetic nanoparticles. In this research detailed examinations of the effect of polyethylene glycol (PEG) on microstructure, size distribution, morphology, magnetic performance and coating of cobalt ferrite nanoparticles (CFO) were conducted. CFO nanoparticles were functionalized by PEG under different conditions, using a facile co-precipitation process. X-ray diffraction (XRD) patterns confirmed that all detected peaks were related to the cubic single-phase spinel structure. Fourier transform infrared spectroscopy (FTIR) revealed the chemical interactions between CFO and PEG. The results of field emission scanning electron microscopy (FE-SEM) showed a uniform spherical morphology with a mean size of 24, 32, and 40 nm at PEG molecular weights of 600, 1500 and 6000, respectively. Furthermore, vibrating sample magnetometer (VSM) revealed that saturation magnetization of nanoparticles decreased by coating with PEG. Results also confirmed that PEG with a higher molecular weight created a thicker coating on CFO. Estimation of capecitabine anticancer drug loading in CFO-PEG nanoparticles investigated by UV-VIS spectroscopy indicated that composite nanoparticles with a PEG molecular weight of 6000 had the highest loading efficiency of 13.67%. Over 40% of capecitabine was released in tumor-like acidic pH (5.5) compared to 23% in normal tissue pH (7.4). Nanoparticles proved blood biocompatible in terms of hemolysis up to a high concentration of 800 μg/ml. Eventually, magnetic resonance imaging (MRI) analyses displayed that CFO-PEG6000 nanoparticles with a relaxivity of 81.12 mM−1 S−1 can be successfully used as an MRI contrast agent. Overall, the developed multifunctional CFO-PEG nanoparticle with potential localized and efficient drug delivery and favorable imaging capability is a promising candidate as a cancer theranostic nanoplatform.
Publisher Copyright: © 2022 Elsevier Ltd and Techna Group S.r.l.
Keywords: Cobalt ferrite; Drug delivery; Magnetic nanoparticles; Polyethylene glycol